Mitos Martandu: Kecendekiaan Lokal Suku Moronene di Kabaena dalam Potensi Banjir di Sungai Lakambula - Heksa Biopsi Puji Hastuti; NFN Rahmawati (Kelasa, 2018)
Martandu Myth is the story of one mythological creature (described as a giant-snake like creature with horns) within Moronene tribe in Kabaena island, precisely in the upstream of Lakambula River. Problems research issued in this article are how the Martandu myth represents the local genius of the Moronene tribe in Kabaena in relation with the flood potential in the Lakambula River and how the relevance of the Martandu Myth is to the present situation. Therefor, the aims of the research are to describe the local genius of Moronene tribe in Kabaena island in relation with flood potential in Lakambula river and to describe the relevance of Martandu Myth to the present situation. Data in the form of Martandu Myth and the reality of the present conditions at the research locus were obtained from literature tracing and interviews with informan. Data were analyzed qualitatively using mitem analysis techniques, readings, and interpretations. The results of the analysis show that the Martandu Myth represents the Moronene tribe in Kabaena local genius in relation to the flood potential in the Lakambula river in the form of a scenario containing a number of layered warnings if someone makes a mistake in violating the rules. In the last section, it is ilustrated when outsiders who want to occupy their wealth come, to be prevented indeed. This myth has relevance to the present situation in which the modernity changes the pattern of thinking of its people to be more instant and feels as if they are no longer fully dependent on the goodness of nature. Likewise, the final scenario of the Martandu against the sharks/marine martandu is relevant to the arrival of people from outside who want to take part in taking advantage of the Moronene earth nature treasure in Kabaena. AbstrakMitos Martandu adalah kisah tentang satu makhluk mitologis (digambarkan sebagai makhluk serupa ular raksasa yang bertanduk) dalam suku Moronene di Pulau Kabaena, tepatnya di hulu Sungai Lakambula. Permasalahan yang diangkat dalam penelitian ini adalah bagaimana mitos Martandu merepresentasikan kecendekiaan lokal suku Moronene di Kabaena dalam kaitannya dengan potensi banjir di Sungai Lakambula dan bagaimana relevansi Mitos Martandu dengan keadaan yang ada sekarang. Dengan demikian, penelitian ini bertujuan mendeskripsikan representasi kecendikiaan lokal suku Moronene di Kabaena dalam Mitos Martandu dalam kaitannya dengan potensi banjir di Sungai Lakambula dan relevansinya dengan keadaan saat ini. Data berupa Mitos Martandu dan realitas kondisi sekarang di lokus penelitian diperoleh dari penelusuran pustaka dan wawancara dengan informan. Data dianalisis secara kualitatif dengan menggunakan teknik analisis mitem, pembacaan, dan pemaknaan melalui perelasian. Hasil analisis menunjukkan bahwa Mitos Martandu merepresentasikan kecendekiaan lokal suku Moronene di Kabaena terkait potensi banjir di Sungai Lakambula dalam bentuk skenario berisi sejumlah peringatan berlapis apabila ada yang melakukan kesalahan melanggar aturan. Pada bagian terakhir, diskenariokan apabila datang pihak luar yang ingin menguasai kekayaan mereka, maka harus dicegah.  Mitos ini memiliki relevansi dengan keadaan sekarang di saat arus modernitas mengubah pola berpikir manusianya menjadi lebih instan dan merasa seolah tidak lagi sepenuhnya bergantung pada kebaikan alam.  Demikian pula skenario akhir martandu yang melawan hiu/martandu laut, relevan dengan kedatangan orang-orang dari  luar yang hendak turut serta mengambil manfaat dari kakayaan alam bumi Moronene di Kabaena.